Microlearning and its contribution to the ability to concentrate in high school students - García-Mendoza, Diógenes (2021)
This study addressed microlearning strategies in the area of ​​mathematics and their impact on concentration. The objective was to analyze microlearning and its contribution to the ability to concentrate in high school students. The research was of a mixed qualitative-quantitative approach; descriptive and correlational type analyzing the variables and their relationship; the population and the sample consisted of 33 high school teachers and two experts on the subject; the methods used were analytical and deductive to respond to the objectives of the work. The instruments used were interviews and surveys. The results obtained indicate that most teachers know and identify this type of strategy, among which the most used are short explanatory videos and readings of small books. It was concluded that they favor concentration by creating meaningful learning, this being an effective and flexible option,